2020
DOI: 10.1126/sciadv.abb5375
|View full text |Cite
|
Sign up to set email alerts
|

Multioctave supercontinuum generation and frequency conversion based on rotational nonlinearity

Abstract: The field of attosecond science was first enabled by nonlinear compression of intense laser pulses to a duration below two optical cycles. Twenty years later, creating such short pulses still requires state-of-the-art few-cycle laser amplifiers to most efficiently exploit “instantaneous” optical nonlinearities in noble gases for spectral broadening and parametric frequency conversion. Here, we show that nonlinear compression can be much more efficient when driven in molecular gases by pulses substantially long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 43 publications
(59 reference statements)
0
28
0
Order By: Relevance
“…Most of the reported experiments have been aimed at pulse compression, and have therefore used atomic noble gases such as argon, krypton, or xenon, to avoid the Raman shift toward longer wavelength that is typically induced by molecular gases' nonlinear response. However, as was demonstrated recently in a number of experiments in gas-filled capillaries, [38,39] molecular gases could be used to simultaneously perform spectral broadening and wavelength shifting of the input pulse.…”
Section: Gas-filled Nonlinear Mpcsmentioning
confidence: 99%
“…Most of the reported experiments have been aimed at pulse compression, and have therefore used atomic noble gases such as argon, krypton, or xenon, to avoid the Raman shift toward longer wavelength that is typically induced by molecular gases' nonlinear response. However, as was demonstrated recently in a number of experiments in gas-filled capillaries, [38,39] molecular gases could be used to simultaneously perform spectral broadening and wavelength shifting of the input pulse.…”
Section: Gas-filled Nonlinear Mpcsmentioning
confidence: 99%
“…[ 20,21 ] This effect is a strong motivation for the development of high‐power few‐cycle drivers, for instance, by the incorporation of advanced nonlinear compression techniques with state‐of‐the‐art ytterbium lasers delivering relatively long pulses (subpicosecond). [ 22,23 ] Finally, since the cut‐off energy scales with the square of the driving wavelength, the fourth knob is the central wavelength of the driver. However, in the single‐atom response, the generated photon flux decreases rapidly with increasing wavelength ( λ −(5–6) ).…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches based on SRS have been reported in gas cells, [ 26,27 ] hollow‐core photonic crystal fibers, [ 28,29 ] and large‐diameter hollow‐core fibers (HCF). [ 22,23,30–32 ] Particularly, in the study by Safaei et al [ 32 ] , we describe a new regime of nonlinear propagation in HCFs that derives from the spatiotemporal nonlinear Raman enhancement observed with subpicosecond driver pulses. This mechanism allows for scaling the peak power by producing broadband, self‐frequency shifted solitons driven by subpicosecond pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Initial observations of the soliton self-frequency shift (SSFS) in gas-filled hollow-core fibers reported small spectral shifts of tens of nanometers [9][10][11]. The SSFS plays a role in several recent studies, especially those of continuum generation and soliton self-compression [12,13]. The interplay of Raman and multimode effects has led to the recent observation of multidimensional solitary states [14].…”
mentioning
confidence: 99%
“…To generate a clean Raman soliton with high efficiency, both the soliton number of the launched pulse and the number of participating Raman transitions should be as small as possible. Several studies have obtained wavelength-tunable sources by extracting the reddest lobe from a supercontinuum [12,13,25]; however, they failed to meet the above conditions and had relatively low efficiency. For example, with N 2 , Carpeggiani et al demonstrated 57 fs pulses with 8 % efficiency in the 1450-1650-nm spectral window.…”
mentioning
confidence: 99%